PERAN HUMAS SEKRETARIAT DPRD DALAM MENJALIN HUBUNGAN SINERGIS ANTARA MEDIA DENGAN DPRD KABUPATEN BULUNGAN - Mujiati .; Aji Ratna Kusuma; Enos Paselle (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aimed to know the role of Bulungan Regency Legislative Secretariat of Public Relations and Protocol in building the relations with media. The data that are presented here are taken from interviews with key informants and informant which is the Head of Public Relations and Protocol with secondary data ,the documents and reports that are relevance to the problems examined. The data analysis technique used is based on interactive model developed by Miles, Huberman and Saldana.